Enhancing self-regulated learning and critical thinking in STEM through flipped classroom models - Setiyawan, Ali Akhmad; Agoestanto, Arief; Isnarto, Isnarto (Jurnal Elemen, 2024)
One of the causes of low proficiency among high school students in mathematical critical thinking is their lack of willingness to learn independently. This study investigated the mathematical critical thinking skills and self-regulated learning of high school students through the Flipped Classroom STEM approach. The research employed a sequential explanatory design, beginning with quasi-experimental pre-tests and post-tests for quantitative assessment of the learning process, followed by qualitative methods such as questionnaires, interviews, and observations for deeper analysis. Data analysis utilized quantitative techniques, including normality and homogeneity tests and hypothesis testing in SPSS, alongside qualitative methods for data reduction, data presentation, and conclusion. The findings revealed that flipped classroom learning significantly improved students' abilities in critical mathematical thinking, particularly highlighting the importance of self-regulated learning. There was a notable difference in post-test scores compared to those from traditional learning methods. Moreover, the study found that students with higher self-regulated learning skills were more effective in critical thinking, underscoring the effectiveness of the flipped classroom approach in fostering independent learning and enhancing essential thinking abilities in mathematics education.